How to paint your boat : painting, varnishing, antifouling - Clegg, Nigel (Sailmate book., 2006)
Most boatowners will find themselves with paintbrush in hand at least once during a season but with the vast range of products now available, how do you know which to select for the job? This book answers all the DIY boatowner's questions, and provides practical advice on painting every type of material. It explains: correct surface preparation; dealing with defects; correct application methods; estimating quantities; drying times; brushes, rollers, pads and sprays; resins, epoxies, solvents and thinners; colour matching. There is also a handy fault-finding section for when things go wrong. '